Screening for Stereopsis of Children Using an Autostereoscopic Smartphone - Yanhui Yang; Huang Wu (Journal of Ophthalmology)
Background. The advantage of using an autostereoscopic smartphone is that it can achieve 3D effects without the need for glasses. The purpose of this study was to evaluate whether this technology could be utilized to detect stereoacuity. Methods. An autostereoscopic smartphone was used to imitate Lang stereotest I & II, Pass Test 3, Dinosaur Stereoacuity Test, and the Random Dot Stereo Acuity Test to screen the stereopsis of children from 3–6 years old. Results. No significant difference was found between each pair of groups (autostereoscopic smartphone vs. Lang stereotest I, Lang stereotest II, Pass Test 3, Dinosaur Stereoacuity Test, and Random Dot Stereo Acuity Test, respectively; Wilcoxon signed-rank test, P value all >0.05). All of the weighted kappa were higher than 0.84. Therefore, all of the comparisons between measurements showed a high level of agreement. Conclusions. The autostereoscopic smartphone is an effective tool when used for the screening of deficiency in stereopsis.